2017
DOI: 10.1177/0954411917746433
|View full text |Cite
|
Sign up to set email alerts
|

Influence of conformity on the wear of total knee replacement: An experimental study

Abstract: Wear of total knee replacement continues to be a significant factor influencing the clinical longevity of implants. Historically, failure due to delamination and fatigue directed design towards more conforming inserts to reduce contact stress. As new generations of more oxidatively stable polyethylene have been developed, more flexibility in bearing design has been introduced. The aim of this study was to investigate the effect of insert conformity on the wear performance of a fixed bearing total knee replacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 46 publications
1
28
2
Order By: Relevance
“…Galvin et al performed a wear test on different conformity designs and found that lower conformity prostheses provided higher contact stresses and smaller contact areas but lower levels of UHMWPE wear. The same results were found by Brockett et al ., who performed a wear test on prostheses with two different degrees of conformity. The authors thought that the higher degree of tibiofemoral conformity would trap the third‐body debris within the prosthetic joint, leading to more severe joint surface damage, and that the constraints of the joint would generate secondary stresses to promote fatigue wear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galvin et al performed a wear test on different conformity designs and found that lower conformity prostheses provided higher contact stresses and smaller contact areas but lower levels of UHMWPE wear. The same results were found by Brockett et al ., who performed a wear test on prostheses with two different degrees of conformity. The authors thought that the higher degree of tibiofemoral conformity would trap the third‐body debris within the prosthetic joint, leading to more severe joint surface damage, and that the constraints of the joint would generate secondary stresses to promote fatigue wear.…”
Section: Discussionmentioning
confidence: 99%
“…The same results were found by Brockett et al ., who performed a wear test on prostheses with two different degrees of conformity. The authors thought that the higher degree of tibiofemoral conformity would trap the third‐body debris within the prosthetic joint, leading to more severe joint surface damage, and that the constraints of the joint would generate secondary stresses to promote fatigue wear. In contrast to the total knee prostheses used in the aforementioned studies, our prosthesis has a highly constrained design that hinders motion and leads to a high contact stress zone.…”
Section: Discussionmentioning
confidence: 99%
“…Less conforming designs with smaller contact area can generate higher peak contact stresses, leading to excessive delamination and failure . In contrast, more conforming designs can reduce peak contact stress; but can lead to increased stresses at the component‐bone interface, increasing the risk of loosening .…”
mentioning
confidence: 99%
“…Conflicting results have been reported on the correlation between polyethylene wear and metal–polyethylene congruency. Several studies have suggested increased wear with reduced conformity; while other studies have shown opposite trends . This may well be because polyethylene wear depends on multiple other factors such as sterilization method, component thickness, sliding distance, cross shear, and material properties.…”
mentioning
confidence: 99%
“…Furthermore, the relative sliding of components and higher compressive load can lead to greater implant wear. More conforming implant designs that provide greater knee stabilization have been shown to have significantly lower wear rates (Brockett et al, 2017;Reinders et al, 2014).…”
Section: Muscle Activation Strategies In the Unstable Kneementioning
confidence: 99%